Multilevel Causal Factors Affecting Collaborative Learning of High School Students - Vijittamrongsak, Virote; Jinnge, Prateep; Pattrawiwat, Kanchana (Journal of Behavioral Science for Development, 2022)
The purpose of this research was to study the multilevel causal factors affecting collaborative learning of high school students. The sample consisted of 545 high school students from 108 study groups in world-class standard schools which selected by multi-stage random sampling. The questionnaires was developed by the researcher from the operational definitions derived from the theories and research concept of the scholars which acceptance criteria were considered for item discrimination (.291-.890), Cronbach’s alpha coefficient (.843-.956), confirmatory factor analysis, multilevel confirmatory factor analysis, inter-rater agreement, and inter-rater reliability. Multilevel structural equation modeling (MSEM) was used for data analysis. The results revealed that the modified multilevel model was fitted with the empirical data (Chi-square = 640.898, df = 402, Chi-square/df = 1.594, CFI = .965, TLI = .959, RMSEA = .033, SRMR (Within) = .033, SRMR (Between) = .066). At the group level, group efficacy had a direct effect on collaborative group learning, and group emotional intelligence had an indirect effect on collaborative group learning through group efficacy. At the individual level, self-efficacy, attitude toward collaborative learning, saraniyadhamma 6, and achievement motivation had a direct effect on collaborative learning, and emotional intelligence had an indirect effect on collaborative learning through self-efficacy, attitude toward collaborative learning and saraniyadhamma 6. In addition, collaborative group learning had a cross-level effect on collaborative learning. Therefore, in organizing activities where students collaborated in groups together, administrators or teachers should promote the development of such important factors that enable students to learn together.